Hubungan Adversity Quotient dengan kinerja karyawan De Chicken di Kota Malang - Tomi Anggara; Fattah Hidayat; Mohammad Bisri (Universitas Negeri Malang, 2021)
The purpose of this study was to determine the relationship between Adversity Quotient and the Performance of De Chicken employees in Malang City. This research is quantitative research using descriptive and correlational analysis. The sampling technique in this study used simple random sampling technique with the number of research subjects of 30 De Chicken employees in Malang City. Data collection uses a scale of Adversity Response Profile with reliability of 0.954 and scale of Performance with reliability of 0.940. The results of this study indicate that as many as 53 percent of De Chicken employees in Malang City have a low Adversity Quotient level and 53 percent of De Chicken employees in Malang City have a high level of performance. Obtained a correlation coefficient of 0.443, it shows that there is a positive relationship between Adversity Quotient and Performance on De Chicken employees in Malang City. Penelitian ini bertujuan untuk mengetahui hubungan Adversity Quotient dengan Kinerja karyawan De Chicken di Kota Malang. Penelitian ini adalah penelitian kuantitatif dengan analisis deskriptif dan korelasional. Teknik simple random sampling digunakan sebagai teknik sampling dengan jumlah subjek penelitian sebanyak 30 karyawan De Chicken di Kota Malang. Skala Adversity Response Profile digunakan sebagai pengumpulan data dengan reliabilitas 0,954 dan skala Kinerja dengan reliabilitas 0,940. Hasil penelitian ini menunjukkan bahwa sebanyak 53 persen karyawan De Chicken di Kota Malang memiliki tingkat Adversity Quotient yang rendah dan 53 persen karyawan De Chicken di Kota Malang memiliki tingkat Kinerja yang tinggi. Diperoleh nilai koefisien korelasi 0,443, hal tersebut menunjukkan bahwa terdapat hubungan yang positif antara Adversity Quotient dengan Kinerja pada karyawan De Chicken di Kota Malang.